An information system for the sport scientific theory of selected sport disciplines - Eder, C.; Strubreither, O.; Kornfeind, P.; Baca, A. (International Journal of Computer Science in Sport, 2002)
An information system is developed to transmit scientific basics of four selected sport disciplines using internet and multimedia technology. The project is funded within the framework of the Research Program "New Media in Education" by the Austrian Federal Ministry for Education, Science and Culture. The aim of the project ("SpInSY") is to arouse the interest in studying theoretical sport scientific concepts more intensively and to obtain a more rapid understanding for complex connections. We expect to improve the interdisciplinary understanding in sport science both in research and education and to achieve a more economic and effective education.